Penerapan Sikap Tanggung Jawab Siswa Pada Pembuatan Karya Seni Menggambar Dekoratif Kelas III SD - Wulandari, Yusnaini; Parmadie, Bambang (JURIDIKDAS, 2025)
This study aims to describe the process of making and applying a responsible attitude in making decorative drawing works of art in class III SD Negeri 57 Bengkulu City. This type of research is a qualitative research with descriptive method. The subjects of this study were third grade students at SD Negeri 57 Bengkulu City. The instruments used in this study were observation sheets, interviews and documentation. Data analysis was carried out by data collection, data reduction, data display, data verification. Data validity uses technical triangulation and member checks. The results of this study were that all groups had followed all stages in the process of making decorative drawing workart. On average, all groups experienced difficulties in determining motives and drawing them. Groups 1, 2, 3 and 4 use bright colors to color their work. During the process of making decorative drawing artwork, almost all students have applied a responsible attitude. Only in groups 2 and 3 were the students noisy and had no focus but were immediately reprimanded by their group mates. Based on the results of the study it can be concluded that the process of making decorative drawing works of art has been carried out by students sequentially and the attitude of responsibility has been described based on the indicators, but there are still deficiencies in its application so it needs improvement in the future.